Bibliometric Study on Metalurgi : Majalah Ilmu Dan Teknologi Published During 2016-2020 - Rochani Nani Rahayu; Yupi Royani (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
This bibliometric studied Metalurgi : Majalah Ilmu dan Teknologi, a serial publication managed by Metallurgical and Materials Research Center LIPI. The data were observed through https://ejurnalmaterialmetalurgi.lipi.go.id/, taking a period from 2016-2020 publications. The data collected and recorded were the number of articles each year, the number of authors, the authors' affiliations, the city where the author works, the most productive authors, and keywords. The data was processed using Ms. Excel and the results of data processing were displayed in table form with the percentage of each variable studied. The study showed that during 2016 - 2020 the Metallurgical Journal published 78 articles, with the highest number of articles written in collaboration with 4 people (17 titles; 21.79%) and at least written collaboratively by 7 people (8 titles; 10.25%). There were 10 articles written individually (12.82%). The mean value of the degree of collaboration is C = 0.87. Efendi Mabruri is the most productive writer with producing 10 titles, the most research institution contributing was LIPI with a frequency of 58 (84.06%), while the most productive college is Sultan Ageng Tirtayasa, 24 (30.76%), and other institutions that contributed to the writing were the Ministry of Industry and PT Petrokimia Gresik. Most authors were living in Tangerang, which is 62 (37.57%). Most keywords are microstructure 15 times (3.51%) and keywords containing Nickel words are 4 (0.95%) Nickel Alloys, Nickel Orees 2 (0.47%), Nickel Plating 2 (0.47%), and Nickel Hydroxide 1 (0.23%).